Student Resilience in Mastering Arabic Vocabulary: A Case Study at Islamic High School Medan - Hidayah, Fadhla Abi; Al-Rasyid, Harun (Universitas Yudharta Pasuruan, 2025)
This study aims to describe the resilience of students in mastering Arabic vocabulary (mufradat) among eighth-grade students at Madrasah Tsanawiyah Islamiyah Medan. This study uses a qualitative approach with a case study design. The research subjects were eighth-grade students, with Arabic teachers as supporting informants. Data were collected through observation, interviews, and documentation, then analyzed using qualitative descriptive methods. The results showed that student resilience was reflected in active perseverance, courage in facing mistakes, emotional regulation skills, and readiness to adjust learning strategies when facing difficulties in mastering mufradat. This resilience is formed through the interaction of internal factors, such as religious motivation and self-confidence, as well as external factors in the form of support from teachers, peers, and a supportive madrasah environment. This study confirms that resilience plays an important role in the successful mastery of vocabulary and needs to be strengthened through adaptive and supportive Arabic language learning practices.